2014
DOI: 10.1111/jch.12390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Pressure Reduction Response and Responder Characteristics to Fixed‐Dose Combination Treatment of Amlodipine and Losartan: A Post Hoc Analysis of Pooled Clinical Trials

Abstract: Data from four clinical trials compared reductions in systolic blood pressure (SBP) and diastolic blood pressure (DBP) among patients treated with amlodipine/losartan 5/50 mg vs 5/100 mg and amlodipine/losartan 5/50 mg vs amlodipine 5 mg and 10 mg. Response rate was assessed as reduction in SBP or DBP (>20/10 mm Hg) and proportion of patients achieving SBP <140 mm Hg or DBP <90 mm Hg. Patients were grouped into quartiles based on baseline SBP and DBP. Mean SBP and DBP were reduced in amlodipine/ losartan 5/50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Amlodipine (68%), among CCBs, and losartan (27%), among ARBs, are the most commonly prescribed antihypertensive agents in each class, according to the Korean healthcare data system. The combination of these two drugs have has been shown to be effective and safe for hypertension management 8,9 . In addition, amlodipine/losartan‐based FDCs have the second longest prescribed history among CCB/ARB‐based SPCs in Korea, and they also have the highest prescribed rates among the CCB/ARB‐based SPCs in three tertiary hospitals of our study.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Amlodipine (68%), among CCBs, and losartan (27%), among ARBs, are the most commonly prescribed antihypertensive agents in each class, according to the Korean healthcare data system. The combination of these two drugs have has been shown to be effective and safe for hypertension management 8,9 . In addition, amlodipine/losartan‐based FDCs have the second longest prescribed history among CCB/ARB‐based SPCs in Korea, and they also have the highest prescribed rates among the CCB/ARB‐based SPCs in three tertiary hospitals of our study.…”
Section: Introductionmentioning
confidence: 59%
“…The combination of these two drugs have has been shown to be effective and safe for hypertension management. 8,9 In addition, amlodipine/losartan-based FDCs have the second longest prescribed history among CCB/ARB-based SPCs in Korea, and they also have the highest prescribed rates among the CCB/ARB-based SPCs in three tertiary hospitals of our study. Moreover, amlodipine/losartanbased SPCs have strong line-up combinations by being available as amlodipine/losartan FDCs for general hypertensive patients, amlodipine/losartan/chlorthalidone for patients with resistant hypertension, and amlodipine/losartan/rosuvastatin FDCs for patients with both hypertension and dyslipidemia, which provide great options to evaluate the efficacy and safety of FDCs for hypertensive patients with broad clinical spectrums.…”
Section: Introductionmentioning
confidence: 65%
“…The same relationship was clinically observed for both amlodipine ( Kario and Shimada, 1997 ) and another calcium antagonist, nifedipine ( Hu et al, 2017 ). A number of experimental studies showed a similar trend towards a greater decrease in SBP and DBP among patients with higher baseline SBP and DBP levels when using other antihypertensive regimens, including therapy with losartan ( Naritomi et al, 2008 ), enalapril or sacubitril/valsartan ( Böhm et al, 2017 ), amlodipine/losartan ( Unniachan et al, 2014 ), and aliskiren or aliskiren/HCTZ ( Black et al, 2010 ). On the other hand, Zheng et al (2011) found a negative correlation of DBP reduction with baseline DBP (while there was no correlation for SBP) in both candesartan and losartan treatment groups.…”
Section: Resultsmentioning
confidence: 90%
“…Unniachan i wsp. [11] przeprowadzili metaanalizę badań z zastosowaniem preparatu złożonego składającego się z losartanu i amlodipiny w porównaniu z monoterapią amlodipiną w dawce 5 mg lub 10 mg. Cel terapeutyczny stanowiło obniżenie stężenia kinazy kreatyny (CTK, creatine kinase) poniżej 140/90 mm Hg lub redukcja SBP o ponad 20 mm Hg albo DBP o więcej niż 10 mm Hg po 8 tygodniach terapii. Wyniki analizy potwierdziły większą skuteczność leczenia złożonego niż monoterapii.…”
Section: Leczenie Skojarzone Arb I Antagonistą Wapniaunclassified